(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The article deals with the problems of formation of spatial thinking and spatial imagination in pupils of VIII-X classes. Psychological and pedagogical aspects of studying drawing by pupils are substantiated. Types and classifications of thinking are given.